Mixture of commercial herbicides based on 2, 4-D and glyphosate mixture can suppress the emergence of zooplankton from sediments. (July 2018) - Portinho, Jorge L.; Nielsen, Daryl L.; Daré, Luana; Henry, Raoul; Oliveira, Régis C.; Branco, Ciro C.Z.
Abstract: It is generally assumed that zooplankton can recolonize lakes that have been exposed to pesticides, via their dormant egg banks. Hitherto, few studies have evaluated the relative importance of dormant egg bank recruitment in the re-establishment of zooplankton communities in the presence of pesticide. This study investigated the effects of commercial products Bratt ® (a.i. 2, 4-D), Roundup ® (a.i. glyphosate) and their mixture on the emergence (abundance and taxon richness) of dormant zooplankton egg banks from natural lake sediment. Sediment samples were collected from the surface sediment (<10 cm depth) in four lakes in Southeast São Paulo, Brazil. We performed a hatching experiment, in which natural lake sediments containing dormant eggs were exposed separately to Bratt ® (applied concentrations ranging from 0.30 to 20 mg L −1 ), Roundup ® (0.28–8.5 mg L −1 ), and combined mixtures of all concentrations, plus one control (non-exposure to formulated herbicides) for a period of 28 days. All tested concentrations of Bratt ®, Roundup ® and their mixture reduced the abundance and taxon richness of emerging zooplankton (except 2 mg L −1 of Bratt ® ). This effect was more pronounced in rotifers. In comparison, there were no negative effects on the emergence of microcrustaceans. These findings suggest that commercial products Bratt ®, Roundup ® and their mixture can suppress the emergence of rotifers, thereby influencing zooplankton recruitment potential in lakes impacted by the presence of these commercial herbicides. Our results stress the importance of the need for additional studies to assess the effects of pesticides on dormant egg banks. Highlights: The dormant eggs represent a major source of regenerative potential in lakes. We examined the effect of Bratt ®, Roundup ® and their mixture on the emergence of the dormant eggs. Herbicides studied reduced the number of zooplankton emerging from the dormant eggs. Herbicides studied can vastly diminish zooplankton populations in lakes.